Emerging Technologies for STEAM Education Full STEAM Ahead - Ge, Xun.; Ifenthaler, Dirk.; Spector, J. Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This theory-to-practice guide offers leading-edge ideas for wide-scale curriculum reform in sciences, technology, engineering, the arts, and mathematics--the STEAM subjects. Chapters emphasize the critical importance of current and emerging digital technologies in bringing STEM education up to speed and implementing changes to curricula at the classroom level. Of particular interest are the diverse ways of integrating the liberal arts into STEM course content in mutually reshaping humanities education and scientific education. This framework and its many instructive examples are geared to ensure that both educators and students can become innovative thinkers and effective problem-solvers in a knowledge-based society. Included in the coverage: Reconceptualizing a college science learning experience in the new digital era. Using mobile devices to support formal, informal, and semi-formal learning. Change of attitudes, self-concept, and team dynamics in engineering education. The language arts as foundational for science, technology, engineering, art, and mathematics. Can K-12 math teachers train students to make valid logical reasoning? Moving forward with STEAM education research.   Emerging Technologies for STEAM Education equips educators, education researchers, administrators, and education policymakers with curricular and pedagogical strategies for making STEAM education the bedrock of accessible, relevant learning in keeping with today's digital advances.      .
Forward.- Introduction to the general problem area and the landscape of various concerns and issues.- What happens when portable devices are introduced in schools and colleges on a large scale?.- What happens when learners are moving from one location to another and working with others who may not be enrolled or following a similar curriculum?.- Education, training, competencies, curricula and technology.- Reconceptualizing a college engineering curriculum based on 21st century skills -- Reconceptualizing a high school science curriculum based on 21st century skills.-  Reconceptualizing a college liberal arts curriculum based on 21st century skills.- Reconceptualizing a middle school mathematics curriculum based on 21st century skills -- Authentic Learning and Meaningful Assessments.- Learning in and about Complex Domains -- Technologies Gone Awry -- Technologies that Show Potential to Improve Learning and Instruction -- Afterword.
Keywords: Educational technology; Learning; Instruction; Educational Technology; Learning & Instruction